Behaviour change programs for abusers: a means to promote the safety of women and children - Chung, Donna (Routledge, 2014)
In this Chapter the development of abuser programs is presented with a discussion of the underpinning theoretical and practice approaches, debates about program success and effectiveness are addressed with reference to the evaluation research and elements of program organisation, practice and reach are critically reviewed in considering the current state of abuser programs.